Identification in simple binary outcome panel data models - Bo E. Honoré; Áureo de Paula (Centre for Microdata Methods and Practice (cemmap), 2021)
This paper first reviews some of the approaches that have been taken to estimate the common parameters of binary outcome models with fixed effects. We limit attention to situations in which the researcher has access to a data set with a large number of units (individuals or firms, for example) observed over a few time periods. We then apply some of the existing approaches to study fixed effects panel data versions of entry games, like the ones studied in Bresnahan and Reiss (1991) and Tamer (2003).
Keywords: 330